Optimal carbon storage during drought - Stefaniak, Elisa Z; Tissue, David T; Dewar, Roderick C; Medlyn, Belinda E (Tree physiology, 2024)
Allocation of non-structural carbohydrates to storage allows plants to maintain a carbon pool in anticipation of future stress. However, to do so, plants must forego use of the carbon for growth, creating a trade-off between storage and growth. It is possible that plants actively regulate the storage pool to maximize fitness in a stress-prone environment. Here, we attempt to identify the patterns of growth and storage that would result during drought stress under the hypothesis that plants actively regulate carbon storage. We use optimal control theory to calculate the optimal allocation to storage and utilization of stored carbon over a single drought stress period. We examine two fitness objectives representing alternative life strategies: prioritization of growth and prioritization of storage, as well as the strategies in between these extremes. We find that optimal carbon storage consists of three discrete phases: ‘growth’, ‘storage without growth’ and the ‘stress’ phase where there is no carbon source. This trajectory can be defined by the time point when the plant switches from growth to storage. Growth-prioritizing plants switch later and fully deplete their stored carbon over the stress period, while storage-prioritizing plants either do not grow or switch early in the drought period. The switch time almost always occurs before the soil water is depleted, meaning that growth stops before photosynthesis. We conclude that the common observation of increasing carbon storage during drought could be interpreted as an active process that optimizes plant performance during stress.